PERANCANGAN DAN ANALISA BIAYA ALAT PENGUJI KEKUATAN TEKAN GENTENG KERAMIK BERGLAZUR - Ucok Mulyo Sugeng (Fakultas teknik Universitas Muhammadiyah Jakarta, 2015)
A quality of a product is a value that leads into customer satisfaction. Good Quality Control system is absolutely necessary as a solution to guarantee the quality of a product. One of the instruments to be used in the system of Quality Control is a test equipment.VDI 2221 design method is used to solve problems and to optimize the use of materials and technology. Several stages of its design are the Clarification of the Task, Conceptual Design, Embodiment Concept and Detail Design.The equipment can be made with standard materials and using available equipment at the workshop. The process of assembly, installation and operation is relatively easy. The chosen one is Varian 1 with maximum pressure 208 bar (212,2 kg/cm2) with total cost Rp. 7.700.000,-.Keywords: customer satisfaction, quality control, VDI 2221